Manganese-pyrochloric acid photosensitizer nanocomplexes against osteosarcoma: achieving both high activatability and high effectiveness - Zhang, Xuran; Wang, Jian; Feng, Qun; Lei, Li; Zhu, Zhiyong (Frontiers in Bioengineering and Biotechnology, 2025)
The application of photodynamic therapy (PDT) is limited by unsatisfactory therapeutic efficacy and dose-dependent phototoxicity in clinic. Intravenous nano-drug delivery systems (NDDSs) hold promise for enhancing the delivery efficiency of photosensitive drugs. Nevertheless, nanocarrier-based NDDSs often result in aggregation-caused quenching effect of photosensitive drugs, failing to site-specific activation. In this study, we exploited the manganese (Mn 2+ )-pyrochloric acid (PPa) nanocomplexes with both high activatability and high effectiveness, which is coordinated using the photosensitizer PPa and metal Mn ion for the treatment of osteosarcoma. The precisely nanocomplexes could be co-assembled in water, stably co-deliver and tumor-specific release of Mn 2+ and PPa, enabling fluorescence recovery. Following laser irradiation, the activated PPa significantly exerts the primary cancer cells-killing effects. Notably, manganese ions Mn 2+ , activating the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway, is observed as a result of maturation of dendritic cells (DCs), augmenting CD8 + -mediated antitumor immune response. Taken together, this study advances on-demand activation of photosensitive drugs and photodynamic immunotherapy toward clinical applicability.